Preclinical evaluation of fenretinide against primary and metastatic intestinal type‑gastric cancer - Ortiz Chaves, Natalia (2024)
In recent years there has been a decline in the incidence of gastric cancer, however the high mortality rate has remained constant. The present study evaluated the potential effects of the retinoid fenretinide on the viability and migration of two cell lines, AGS and NCI‑N87, that represented primary and metastatic intestinal gastric cancer subtypes, respectively. It was determined that a similar dose of fenretinide reduced the viability of both the primary and metastatic cell lines. In addition, it was demonstrated that combined treatment with fenretinide and cisplatin may affect the viability of both primary and metastatic gastric cancer cells. Furthermore, a wound healing assay demonstrated an inhibitory effect for fenretinide on cell migration. As part of the characterization of the mechanism of action, the effect of fenretinide on reactive oxygen species production and lipid droplet content was evaluated, with the latter as an indirect means of assessing autophagy. These results support the hypothesis of combining using fenretinide with conventional therapies to improve survival rates in advanced or metastatic gastric cancer.